STUDI ANALISIS SEDIMENTASI DI SUNGAI PUTE RAMMANG-RAMMANG KAWASAN KARST MAROS - Andirah Al Ansar; Muhammad Arsyad; Sulistiawaty Sulistyawaty (Universitas Negeri Makassar, 2014)
Research on sedimentation analysis in Pute river at Rammang-Rammang Maros Karst Region aims to calculate suspended load and bed load, describing sedimentation rate, and analyze the types of sediment contained in Pute river. Water samples of Pute River water were taken using by water sample sediment tool. Sampling was conducted at two points called the dock I (4 ° 55'59,02